Trimebutine, a small molecule mimetic agonist of adhesion molecule L1, contributes to functional recovery after spinal cord injury in mice - Junping Xu; Chengliang Hu; Qiong Jiang; Hongchao Pan; Huifan Shen; Melitta Schachner (The Company of Biologists, 2017)
Curing spinal cord injury (SCI) in mammals is a daunting task because of the lack of permissive mechanisms and strong inhibitory responses at and around the lesion. The neural cell adhesion molecule L1CAM (L1) has been shown to favor axonal regrowth and enhance neuronal survival and synaptic plasticity but delivery of full-length L1 or its extracellular domain could encounter difficulties in translation to therapy in humans. We have, therefore, identified several small organic compounds that bind to L1 and stimulate neuronal survival, neuronal migration and neurite outgrowth in an L1-dependent manner. Here, we assessed the functions of two L1 mimetics, trimebutine and honokiol, in regeneration following SCI in young adult mice. Using the Basso Mouse Scale (BMS) score, we found that ground locomotion in trimebutine-treated mice recovered better than honokiol-treated or vehicle-receiving mice. Enhanced hindlimb locomotor functions in the trimebutine group were observed at 6 weeks after SCI. Immunohistology of the spinal cords rostral and caudal to the lesion site showed reduced areas and intensities of glial fibrillary acidic protein immunoreactivity in both trimebutine and honokiol groups, whereas increased regrowth of axons was observed only in the trimebutine-treated group. Both L1- and L1 mimetic-mediated intracellular signaling cascades in the spinal cord lesion sites were activated by trimebutine and honokiol, with trimebutine being more effective than honokiol. These observations suggest that trimebutine and, to a lesser extent under the present experimental conditions, honokiol have a potential for therapy in regeneration of mammalian spinal cord injuries.